Democracy in practice ceremony and ritual in parliaments - Rai, Shirin 1960-; Johnson, Rachel E. (Palgrave Macmillan, 2014)
"This collection highlights the ways in which parliaments create and maintain powerful symbols of democracy and power. It explores how political and social hierarchies operate within parliaments through ceremonial spectacles, formal and informal rules and rituals, art and architecture. Members are socialized through everyday practices but such institutional disciplining is also challenged performatively - by refusal to participate, by subversion of norms or by rejection of rules. The contributions to this volume highlight that the everyday ritual practices as well as institutional ceremonies have significant political meaning, whether their focus is upon the spectacular or the quotidian. Chapters on opening ceremony, Prime Minister's Questions, on performance of debate and disruption, on the architecture and space of suggest that what has often been seen as the banal backdrop to politics proper, accumulated tradition or necessary rules of procedure, should in fact be the starting-point for our analyses of modern democratic parliaments"--